Anaphylaxis: clinical features and GP's role in management. Issue 18 (19th September 2014) - Sellaturay, Priya; Rutkowski, Krzysztof; Nasser, Shuaib
<x xml:space="preserve">Abstract</x> Anaphylaxis can be fatal if not treated promptly and it is important to identify likely triggers and educate patients on the proper use of adrenaline autoinjector. Here, the authors outline the clinical features, acute and long‐term treatment and the GP's role in management.